The 6-GHz Multibeam Maser Survey – III. Comparison between the MMB and HOPS. Issue 3 (5th December 2017) - Breen, S L; Contreras, Y; Ellingsen, S P; Green, J A; Walsh, A J; Avison, A; Longmore, S N; Fuller, G A; Voronkov, M A; Horton, J; Kroon, A
Abstract: We have compared the occurrence of 6.7- and 12.2-GHz methanol masers with 22-GHz water masers and 6035-MHz excited-state OH masers in the 100 deg 2 region of the southern Galactic plane common to the Methanol Multibeam and H2 O southern Galactic Plane Surveys. We find the most populous star formation species to be 6.7-GHz methanol, followed by water, then 12.2-GHz and, finally, excited-state OH masers. We present association statistics, flux density (and luminosity where appropriate) and velocity range distributions across the largest, fully surveyed portion of the Galactic plane for four of the most common types of masers found in the vicinity of star formation regions. Comparison of the occurrence of the four maser types with far-infrared dust temperatures shows that sources exhibiting excited-state OH maser emission are warmer than sources showing any of the other three maser types. We further find that sources exhibiting both 6.7- and 12.2-GHz methanol masers are warmer than sources exhibiting just 6.7-GHz methanol maser emission. These findings are consistent with previously made suggestions that both OH and 12.2-GHz methanol masers generally trace a later stage of star formation compared to other common maser types.